Enhanced detection of Porcine reproductive and respiratory syndrome virus in fixed tissues by in situ hybridization following tyramide signal amplification. (May 2015) - Trang, Nguyen Thi; Hirai, Takuya; Ngan, Pham Hong; Lan, Nguyen Thi; Fuke, Naoyuki; Toyama, Keiko; Yamamoto, Tsukasa; Yamaguchi, Ryoji
This study evaluated the sensitivity of biotinyl–tyramide-based in situ hybridization (TISH) method by comparison with chromogenic in situ hybridization (CISH) and immunohistochemical staining (IHC) methods. This study also determined the effect of fixative and fixation time on the detection of Porcine reproductive and respiratory syndrome virus (PRRSV) in paraffin-embedded tissues. Lung samples were fixed in 4% paraformaldehyde (PFA) or 10% neutral buffered formalin (NBF) for various times before paraffin embedding. Of 30 paraffin-embedded lung samples, fixed for 1 day in 4% PFA or 10% NBF, 18 (60%) were positive for PRRSV by nested reverse transcription polymerase chain reaction (nRT-PCR). All 18 lung samples (100%) also were positive for PRRSV by TISH, but only 10 of these 18 specimens (56%) were positive for PRRSV by IHC and CISH. We demonstrated that TISH can detect PRRSV RNA in paraffin-embedded tissues after up to 90 days of fixation. PRRSV nucleic acids and antigens were better preserved in 4% PFA than in 10% NBF. Compared with CISH and IHC testing methods, TISH appeared to be more sensitive for the detection of PRRSV in paraffin-embedded tissues.